Carbon nanosheets derived from soluble pitch molecules and their applications in organic transistors - Lee, Jae-Seon; Joh, Han-Ik; Kim, Tae-Wook; Lee, Sungho (ELSEVIER, 2014)
We report a synthesis method for carbon nanosheets (CNSs) using pitch prepared by reforming a commercially available naphtha cracking bottom oil, which is often used as a carbon fiber precursor. The pitch solution is spin-coated on a silicon wafer without using a catalyst support. After stabilization and carbonization, the CNSs as thin as 2 nm show an electrical conductivity of approximately 30,000 S/m. Although the CNSs do not have a well-developed graphitic structure, as observed using Raman spectroscopy and transmission electron microscopy, they are conductive enough for use as electrodes in an organic thin film transistor. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: GRAPHENE; FIBERS; XPS